MANOR’S REALITY IN THE LEXICO-SEMANTIC SYSTEM OF LANGUAGE - Hannah M. Udovichenko (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
and inherits from its descendants. It is the embodiment of the culture of the people, psychological features, its identifying element. In the process of communication, even people who speak the same language equally well have problems in mutual understanding, because they are representatives of different cultures and, accordingly, different perceptions, worldviews of the same things and phenomena. The array of classical literature until the middle of the twentieth century often contains the realities associated with the typical place of residence called “manor”, which determined not only the material and social but also the cultural level of society at that time. The purpose of this article is to determine the place of “reality” in the lexical-semantic system of language, analysis of the problem of translation of historical, namely manor’s realities in the peace of writing. Any national culture consists of national and international units. For each culture, the international, or borrowed units will be their own, and in the case of comparing two cultures, the international units of each pair of cultures will be different. Only in the presence of general background knowledge, or the ability to clearly explain the difference to each other, communicators will be able to understand each other. Because background knowledge is known to all members of the national community it forms the part of the mass culture on which writers rely. Background knowledge as an element of mass culture, obeying its general pattern, is divided into relevant and background knowledge of cultural heritage, to which we can attribute the realities. The study found that realities are words or expressions that denote objects, concepts, situations that do not exist in the practical experience of people who speak other languages. The realities are various factors studied by foreign linguistics and translation studies, such as the state system of a given country, the history and culture of a given people, linguistic contacts of native speakers of this language and so on in terms of their reflection in this language. These include objects of material culture, which serve as the basis for the nominative meaning of the word, as well as words that denote national-specific features of life and everyday life. In connection with the way of life of “family seat”, the manor’s realities of both realitiesobjects and realities-words occupied an important place in the lives of people of the 18th – 19th centuries, which could not help but be reflected in the literature of that time, which is significant historical and cultural value, and enjoys, moreover, interest from the modern reader. The translation of such realities causes certain difficulties in the work of the translator and requires additional study and analysis. Thus, we have two types of difficulties. First, it is the translation of manor’s realities as historical for today’s reader, and secondly, the actual process of translation due to the difference in concepts spoken in different languages. To solve this problem, it is necessary to take any work with a sufficient number of manor’s realities, its translation or translations and to classify the found realities, evaluate how they were translated, and what is better to use in the future, and what is a bad example for future translators